Importance of branding for property developers in Malaysia. - Cheng, Fan Fah; Cheok, Jason (2008)

(untitled)
This paper aims to study the brand consciousness of property purchasers in Malaysia. This study is based on a survey of purchasers in Klang Valley on the brand awareness and the brand personality traits of property developers. 5000 questionnaires were distributed and finally 214 were used for this study. The results show that property purchasers are brand conscious in relation to the property developers and they ranked developers based on the brand personality. Property purchasers look at trend, professionalism and investment as the top 3 priorities in the property brand. The conclusion is that all property firms, designers, real estate agents and stakeholders who/that are involved in property development are to ensure that their products are designed with brand consciousness in mind. The findings in this paper suggest that property designers should pay attention to trend in the property development, property marketers should be professional in dealing with purchasers and the developers should ensure good locations for property investments.